Investigation of super-radiant Smith-Purcell radiation from double grating and DC beam - Karataev P. V. Pavel Vladimirovich; Lekomtsev K. Konstantin; Kubankin A. S. Aleksandr Sergeevich; Nazhmudinov R. M. Ramazan Magomedshapievich; Potylitsyn A. P. Alexander Petrovich; Shipulya M. A. Mikhail Alekseevich; Vukolov A. V. Artem Vladimirovich (2016, 2016)
Title screen